Association between smoking habits and lung function among adult smokers: A cross-sectional study in public health - Hermanto, Andrik; Masroni, Masroni; Melana, Leonard Ivan T.; Yufenanda, Michelle Mayang (The Journal of Palembang Nursing Studies, 2025)
Background: Smoking is a major risk factor for impaired lung function. Continuous exposure to cigarette smoke in adulthood contributes to a progressive decline in lung capacity, which may lead to chronic respiratory diseases and other serious health complications. While previous studies have used indirect tools such as smokelyzers, limited research has applied spirometry to directly evaluate lung function among smokers in community health settings. Objective: This study aimed to analyze the relationship between smoking habits and lung function, measured using spirometry, among adult smokers. Methods: A cross-sectional design was conducted in a public health center. Smoking behavior was assessed using the Glover-Nilsson Smoking Behavioral Questionnaire (GN-SBQ), while lung function was measured with spirometry. Data were analyzed using the Spearman rank correlation test. Results: The study included 50 adult respondents with a mean age of 40.8 ± 11.1 years. Most participants demonstrated strong smoking behavior, with 41 respondents (69.5%) categorized as very strong and 24 respondents (40.7%) categorized as moderate. Spirometry results indicated a significant negative correlation between smoking behavior and lung function (p = 0.010; r = –0.360). These findings suggest that greater smoking intensity is associated with reduced lung capacity, reflecting the harmful cumulative effects of tobacco exposure. Conclusion: Smoking habits were significantly associated with decreased lung function among adult smokers. This highlights the need for preventive efforts, including health education, routine lung function screening, and smoking cessation programs in public health settings to mitigate long-term respiratory complications.